Interest to learn music among secondary school students: a case study of SMK Seksyen 19, Shah Alam / Azli Abdul Rahman - Abdul Rahman, Azli (2008)
This study looks at a small group of secondary students in SMK Seksyen 19, Shah Alam. Factors which affect interest to learn music in school is investigated. Samples of 10 students were selected from among music classes in Form 1 and Form 2. Data was collected through interviews with five male and five female students. Students were asked their perceptions o f how their personal interest in music, parents, peers, the school, the teacher and the facilities have affected their interest to learn music in school. Results indicate that all these factors do play a role in their perceptions towards learning music. However, it was found that the most important factor which influences their interest is their own personal believes and liking for music. Problems faced while learning music, such as limitations in instruments, facilities and teacher personalities although present, did not give a big impact in their learning process, as they found learning music enjoyable and interesting. Generally, it can be summarized that the students in this school became more interested to learn music as time passes although they initially did not choose to take the subject as an elective.